Recommended Guidelines for the Conduct and Evaluation of Prognostic Studies in Veterinary Oncology - Webster, J. D.; Dennis, M. M.; Dervisis, N.; Heller, J.; Bacon, N. J.; Bergman, P. J.; Bienzle, D.; Cassali, G.; Castagnaro, M.; Cullen, J.; Esplin, D. G.; Pena, L.; et al. (Sage Publications Inc, 2011)
There is an increasing need for more accurate prognostic and predictive markers in veterinary oncology because of an increasing number of treatment options, the increased financial costs associated with treatment, and the emotional stress experienced by owners in association with the disease and its treatment. Numerous studies have evaluated potential prognostic and predictive markers for veterinary neoplastic diseases, but there are no established guidelines or standards for the conduct and reporting of prognostic studies in veterinary medicine. This lack of standardization has made the evaluation and comparison of studies difficult. Most important, translating these results to clinical applications is problematic. To address this issue, the American College of Veterinary Pathologists' Oncology Committee organized an initiative to establish guidelines for the conduct and reporting of prognostic studies in veterinary oncology. The goal of this initiative is to increase the quality and standardization of veterinary prognostic studies to facilitate independent evaluation, validation, comparison, and implementation of study results. This article represents a consensus statement on the conduct and reporting of prognostic studies in veterinary oncology from veterinary pathologists and oncologists from around the world. These guidelines should be considered a recommendation based on the current state of knowledge in the field, and they will need to be continually reevaluated and revised as the field of veterinary oncology continues to progress. As mentioned, these guidelines were developed through an initiative of the American College of Veterinary Pathologists' Oncology Committee, and they have been reviewed and endorsed by the World Small Animal Veterinary Association.
Keywords: cancer; guidelines; prognostication; standardization; veterinary oncology